2014
DOI: 10.9790/0853-13477480
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Anemia among pregnant women attending antenatal clinic in Dr. Prabhakar Kore hospital, Karnataka-A Cross sectional study

Abstract: Background and Objectives: Anemia in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
15
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 4 publications
10
15
2
4
Order By: Relevance
“…In contrast to this study a study conducted at Karnataka showed that significant association between knowledge regarding causes, sign and symptoms of anemia, knowledge regarding proper diet to prevent anemia and status of anemia. 21 Similarly finding contrast to the study done in India reveals overall 76.5% of the participants had good knowledge regarding anemia and it association to anemia status. 22 The finding of this study revealed that the inter pregnancy difference was significantly association with anemia (OR=2.732, 95% CI=1.3355.591, p=0.005).…”
contrasting
confidence: 54%
“…In contrast to this study a study conducted at Karnataka showed that significant association between knowledge regarding causes, sign and symptoms of anemia, knowledge regarding proper diet to prevent anemia and status of anemia. 21 Similarly finding contrast to the study done in India reveals overall 76.5% of the participants had good knowledge regarding anemia and it association to anemia status. 22 The finding of this study revealed that the inter pregnancy difference was significantly association with anemia (OR=2.732, 95% CI=1.3355.591, p=0.005).…”
contrasting
confidence: 54%
“…A similar study from Karnataka also showed that knowledge regarding anemia and healthy diet was poor among pregnant women. 3 Other studies have also indicated that nutritional knowledge was remarkably low in pregnant women. 4 A study comparing nutritional awareness between urban and rural mothers showed that rural mothers were not aware of the consequences of inadequate nutrition during pregnancy 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the study participants were in the age group of 21-25 years (77.4%), primi (56.0%), belonged to lower middle class (75.0%), educated up to high school (52.0%) and followed Hindu religion (94.0%). Higher proportion of educated participants had a better pre-test knowledge score as compared to those who are less educated (76.9% of Graduates and above had good score against 12.5% of participants with education of primary and middle school, p value <0.001) and higher proportion of participants in higher socio economic class had a better pre-test knowledge score as compared to those who are in lower socio economic classes (83.3% of the participants in upper class good score vs. 50% in lower middle class and 0% among participants in lower class, p value <0.001) In the present study overall pretest score of the study participants ranged from fair (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) to good (21-30) in 49.4% and 46.4% of them respectively. Baby A et al, in their research work conducted in Karnataka observed that the majority of the antenatal mothers (54%) had satisfactory knowledge, 38% had poor knowledge, and 8% had good knowledge regarding anemia during pregnancy.…”
Section: Discussionmentioning
confidence: 45%